Cervical plexus block as an alternative anesthetic approach for type I thyroplasty: a case report - Abi Lutfallah,Antoine (2020)
Abstract Background: The role of type I thyroplasty (TIP) is well established as the treatment for glottal insufficiency due to vocal fold paralysis, but the ideal anesthetic management for this procedure is still largely debated. We present the case of a novel anesthetic approach for TIP using combined intermediate and superficial Cervical Plexus Block (CPB) and intermittent mild sedation analgesia. Case report: A 51-year-old presenting with left vocal fold paralysis and obstructive sleep apnea was scheduled for TIP. An ultrasound-guided intermediate CPB was performed using the posterior approach, and 15 mL of ropivacaine 0.5% were injected in the posterior cervical space between the sternocleidomastoid muscle and the prevertebral fascia. Then, for the superficial CPB, a total of 10 mL 0.5% ropivacaine was injected subcutaneously, adjacently to the posterior border of the sternocleidomastoid muscle, without penetrating the investing fascia An intermittent sedation analgesia with a target-controlled infusion of remifentanyl (target 0.5 ng.mL-1) was used to facilitate prosthesis insertion and the fiberoptic laryngoscopy. This technique offered a safe anesthetic airway and good operating conditions for the surgeon, as well as feasible voice monitoring and optimal patient comfort. Conclusion: The use of a regional technique is a promising method for the anesthetic management in TIP, especially in patients with compromised airway.